2009
DOI: 10.1007/s00232-009-9169-1
|View full text |Cite
|
Sign up to set email alerts
|

Triacontanol and Jasmonic Acid Differentially Modulate the Lipid Organization as Evidenced by the Fluorescent Probe Behavior and 31P Nuclear Magnetic Resonance Shifts in Model Membranes

Abstract: Fluorescence resonance energy transfer (FRET), time-resolved fluorescence and anisotropy decays were determined in large unilamellar vesicles (LUVs) of egg phosphatidylcholine with the FRET pair N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)-1,2-dipalmitoyl-sn-glycero-3-phospho-ethanolamine as donor and lissamine rhodamine B 1,2-dipalmitoyl-sn-glycero-3-phosphoethanolamine as acceptor, using 2-ps pulses from a Ti:sapphire laser on LUVs with incorporated plant growth regulators: triacontanol (TRIA) and jasmonic acid (JA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…NO supplied exogenously provides resistance against stress induced by HMs like Cd in rice (Panda et al 2011) and As in fescue (Jin et al 2010). There is some evidence that the exogenous application of TRIA inhibited lipid peroxidation in spinach and peanut plants' (Ramanarayan et al 2000;Verma et al 2011) leaves and improved membrane integrity by differentially modulating membrane lipid composition (Swamy et al 2009). Perveen et al (2011) found that TRIA-induced improvement in growth might have been due to its effect on the performance of antioxidant enzymes like POD under salt stress (Perveen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…NO supplied exogenously provides resistance against stress induced by HMs like Cd in rice (Panda et al 2011) and As in fescue (Jin et al 2010). There is some evidence that the exogenous application of TRIA inhibited lipid peroxidation in spinach and peanut plants' (Ramanarayan et al 2000;Verma et al 2011) leaves and improved membrane integrity by differentially modulating membrane lipid composition (Swamy et al 2009). Perveen et al (2011) found that TRIA-induced improvement in growth might have been due to its effect on the performance of antioxidant enzymes like POD under salt stress (Perveen et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…S-24; however, foliar-applied TRIA at different growth stages decreased oxidative stress-induced membrane damage, which is apparent from the stressinduced reduction in MDA content (a product of lipid peroxidation) and H 2 O 2 (most stable ROS in plants) in both wheat cultivars. TRIA inhibited lipid peroxidation in spinach (Spinacea oleracea L.) (Ramanarayan et al, 2000) and Arachis hypogaea L. (Verma et al, 2011) leaves and improved membrane integrity by differentially modulating membrane lipid composition (Swamy et al, 2009). In the present study, TRIA-induced improvement in growth might have been due to its effect on the performance of antioxidant enzymes like POD under salt stress Ertani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…TRIA suppresses the stress-related genes and up-regulates the genes involved in enhanced antioxidant enzymes and nitrogen metabolism enhanced by the formation of various organic compounds (Ertani et al, 2012) and it works as a best antioxidizing mediator ) and stoutly inhibits the collapse of lipid peroxidation of both nonenzymatic and enzymatic reactions (Ramanarayan et al, 2000). TRIA modulates the membrane's lipid chemical composition by changing its organization (Swamy et al, 2009) and enhances the level of polyunsaturated fatty acids (Shripathi and Swamy, 1994). In parallel to our results, foliar application of TRIA enhanced the activity of POD in wheat (Perveen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…TRIA strongly inhibits the breakdown of both non-enzymatic and enzymatic lipid peroxidation in chloroplast thylakoid membranes (Ramanarayan et al, 2000) and also works as a better-quality antioxidising agent . TRIA modulates the membrane's lipid chemical composition by changing its organization (Swamy et al, 2009) and enhances the level of polyunsaturated fatty acids (Shripathi and Swamy, 1994). Under saline regimes foliar application of TRIA suppresses the stress-related genes and up-regulates the genes involved in the photosynthesis process, enhances mineral nutrients and water uptake, enhances the activities of antioxidant enzymes for proper regulation of the metabolic processes, as well as nitrogen metabolism upregulated by the formation of various organic compounds (Ertani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%